MENCARI AKAR PENYEBAB KEKERASAN DALAM RUMAH TANGGA TERHADAP PEREMPUAN TIONGHOA DI JAWA TENGAH - Pramudya Pramudya (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The Act No 23/2004 is a public policy in attempt to eliminate domestic violence. It mostly contains Positivist’s values of human rights and gender equality which are imposed to Tionghoa Society. In contrast, Tionghoa society’s legal culture values Patriarchy, Confucianism and Christianity, in which gender inequality is acceptable. Consequently, this Act is not effectively implemented. Key words: public policy, discrepancy of values, legal culture.